The Efficacy of the Anagram Technique in Stimulating EFL Learners’ Creativity and Enhancing Vocabulary Mastery: An Empirical Evidence - Lamadjido, Muhammad Reski; Suriaman, Aminah; Agussatriana, Agussatriana (Journal of Language and Literature Studies, 2025)
This study investigates the effectiveness of the Anagram technique in enhancing vocabulary mastery among tenth-grade students of Islamic High Schools. Vocabulary acquisition plays a pivotal role in mastering English, yet many students struggle with retention and application. This quasi-experimental research aimed to assess whether the Anagram technique, which involves rearranging scrambled letters to form meaningful words, could improve students’ mastery of nouns, verbs, and adjectives. The study involved two groups: an experimental group, which received instruction using the Anagram technique, and a control group, which followed conventional vocabulary instruction. A pre-test and post-test were administered to both groups to measure improvements in vocabulary proficiency. The results showed that the experimental group exhibited a significant improvement in vocabulary mastery, with their mean score increasing from 65 to 74, while the control group showed only a minimal increase from 69 to 70. The t-test analysis confirmed the statistical significance of the difference (t-count = 11.298 > t-table = 1.995), indicating that the Anagram technique was more effective than traditional methods. These findings highlight the potential of using interactive, puzzle-based activities in language instruction to enhance students' cognitive engagement and retention of vocabulary. The study suggests that integrating word-play strategies like Anagram into EFL classrooms can foster active learning and provide an engaging alternative to traditional vocabulary teaching methods, benefiting students’ long-term vocabulary development.